Probiotic Enterococcus faecium CRL 183 inhibit chemically induced colon cancer in male Wistar rats - Sivieri, Katia [UNESP]; Spinardi-Barbisan, A. L. T. [UNESP]; Barbisan, Luis Fernando [UNESP]; Bedani, R. [UNESP]; Pauly, N. D. [UNESP]; Carlos, Iracilda Zeppone [UNESP]; Benzatti, F. [UNESP]; Vendramini, Regina Célia [UNESP]; Rossi, Elizeu Antonio [UNESP] (Springer, 2008)
Several animal studies have shown that supplementation with specific strains of lactic acid bacteria could prevent the establishment, growth, and metastasis of transplantable and chemically induced tumors. The goal of this study was to determine the effect of Enterococcus faecium CRL 183 on the incidence of colorectal tumors induced experimentally by dimethylhydrazine (DMH). We used thirty 4-week old male Wistar rat. The animals belonging to the DMH groups were injected s.c 20 mg/kg body weight of 1,2 dimethylhydrazine and 1 mM EDTA (pH 6.5), in a weekly dose, for 14 weeks. Three groups were used: (1) Control (not initiated); (2) Initiated with DMH; (3) Initiated with DMH + intake of E. faecium CRL 183. At the end of the 42nd week, all the animals were euthanized; the colons were removed and analyzed histologically. All the groups were compared histologically and IL-4, IFN-gamma and TNF-alpha cytokines. The control group did not develop pre-neoplastic lesions. The E. faecium CRL 183-DMH group showed a 50% inhibition in incidence in average number of tumors (P < 0.001), reduced the formation of ACF (P < 0.001), the lowest number of adenocarcinoma being found in this group (P < 0.001) and enhanced the immune response by increasing IL-4, IFN-gamma and TNF-alpha (P < 0.001) when compared with the DMH group.
Keywords: Colon cancer; Probiotic; Enterococcus faecium; Rat; Dimethylhydrazine